2020
DOI: 10.1016/j.jctube.2019.100141
|View full text |Cite
|
Sign up to set email alerts
|

Phase III, placebo-controlled, randomized, double-blind trial of tableted, therapeutic TB vaccine (V7) containing heat-killed M. vaccae administered daily for one month

Abstract: ObjectiveImmunotherapy of tuberculosis (TB) to shorten treatment duration represents an unmet medical need. Orally delivered, tableted TB vaccine (V7) containing heat-killed Mycobacterium vaccae (NCTC 11659) has been demonstrated in prior clinical studies to be safe and fast-acting immune adjunct.MethodsThe outcome of Phase III trial of V7 containing 10 µg of hydrolyzed M. vaccae was evaluated in 152 patients randomized at 2:1 ratio: V7 (N = 100), placebo (N = 52). Both arms received conventional 1st or 2nd li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 35 publications
0
12
0
2
Order By: Relevance
“…TB represents a global health problem that is further aggravated by malnutrition and poor hygiene in developing countries, and is one of the most common co-infections and causes of death among human immunodeficiency virus (HIV)-infected individuals [ 142 ]. Moreover, certain M. tuberculosis strains are known to cause difficult-to-treat infections such as multi-drug-resistant [ 143 ], extremely drug resistant, and totally drug resistant TB [ 96 , 144 ], overall generating high socioeconomic burden [ 43 ]. Therefore, there is a clear unmet need for developing novel and effective drugs for the prevention and treatment of TB.…”
Section: History Of Mycobacterium Vaccae Nctc 11659 Researchmentioning
confidence: 99%
“…TB represents a global health problem that is further aggravated by malnutrition and poor hygiene in developing countries, and is one of the most common co-infections and causes of death among human immunodeficiency virus (HIV)-infected individuals [ 142 ]. Moreover, certain M. tuberculosis strains are known to cause difficult-to-treat infections such as multi-drug-resistant [ 143 ], extremely drug resistant, and totally drug resistant TB [ 96 , 144 ], overall generating high socioeconomic burden [ 43 ]. Therefore, there is a clear unmet need for developing novel and effective drugs for the prevention and treatment of TB.…”
Section: History Of Mycobacterium Vaccae Nctc 11659 Researchmentioning
confidence: 99%
“…However, it cannot be used repeatedly because it will induce a nonspecific humoral response that will enhance cancer progression. In an attempt to overcome this limitation, Standford and Rook developed a programme for improved agents that could replace BCG in the control of Tuberculosis and noted that heat killed Mycobacterium vaccae had the ability to enhance TH-1 responses and suppress the humoral response, making it a therapeutic agent in its own right (Bourinbaiar et al, 2019). Further research showed that Mycobacterium obuense was superior to M. vaccae and was much easier to manufacture with good manufacturing practice standards.…”
Section: Adjuvants Are Not Secondary Considerationsmentioning
confidence: 99%
“…vaccae ™ vaccine is a lysate comprised of inactivated Mycobacterium vaccae (non-tuberculous mycobacteria) developed as an immunotherapeutic agent to help shorten TB treatment for patients with drug-susceptible TB and licensed by the China Food and Drug Administration (FDA). A Phase III study of efficacy has been recently published [2,62] (Figures 2 and 3).…”
Section: Inactivated Whole-cell Mycobacteriamentioning
confidence: 99%
“…Since the majority of the adolescent and adult population in countries endemic of TB has been previously vaccinated with BCG at birth, what is sought with subunit candidates comprising specific Mtb antigens is to potentiate the pre-existing immunity induced by BCG [2, 46,62]. Recent studies indicate that new TB vaccines that are compared to BCG should be interpreted cautiously with reference to a specific BCG formulation and not presumed to generalize to all BCGs [13].…”
Section: Target Population For a New Tb Vaccinementioning
confidence: 99%